Evaluation of Hevea clones in the mature phase under the agroclimate of Sub-Himalayan West Bengal - Das G; Chaudhuri D; Varghese Y A (Journal of Plantation Crops, 2010)
Multidisciplinary evaluation of eighteen different clones of Hevea was initiated during 1990 at the Regional Experiment Station, Nagrakata, West Bengal to screen clones well adapted to the specific environmental condition of the region. At the time of panel opening for tapping, none of the clones were found to be superior in girth compared to the check clone RRII 105. However, girth was significantly higher in Haiken 1, RRIM 612, SCATC 93/114 and RRIM 703 compared to RRII 105. The bole volume of the clones varied from 0.07 to 1.1 m3. Among the clones evaluated, RRII 208 and SCATC 88/13 were the top rankers in terms of annual yield over nine years followed by RRIM 605. The winter yield contribution of RRII 208 and SCATC 88/13 was above 59;. The pattern of yield in both panels was superior in RRII 208, SCATC 88/13 and RRIM 605 compared to the check clone. Percentage of plants showing severe tapping panel dryness (80-100;occurrence) was high in SCATC 88/13 (19) followed by RRII 203 (15) and RRIM 612 (13) and minimum in RRII 208 and RRIM 605 (2). In general, wind damage was high among the clones with RRIM 605 recording the highest incidence followed by RRII 300, RRII 208, GT 1 and SCATC 93/114. The clones RRII 208, SCATC 88/13 and RRIM 605 were found to be the promising clones for this region.
Keywords: Agro-climatic factors; Clone evaluation; Seasonal effect